Empowering MSMEs in Bali through Financial Technology and Digital Payment Innovation to Enhance Global Competitiveness - Permana, Dewa Gde Yoga; Wirayudha, I Gede Bayu; Putra, I Putu Dharmawan Suryagita Susila (Telaah Bisnis, 2025)
This study aims to analyze the impact of Financial Technology (FinTech) and Digital Payment Innovation on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Bali. This research employs a quantitative approach with Ordinary Least Squares (OLS) regression analysis to examine the relationship between FinTech usage, digital payment innovation, and MSME competitiveness. Data were collected from 100 MSME owners across various sectors in Bali, using structured questionnaires and direct interviews. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, were performed to ensure the robustness of the regression model. The research results show that FinTech usage and digital payment innovation significantly and positively affect MSME competitiveness, with an R-squared value of 0.605, indicating that the two independent variables can explain 60.5% of the competitiveness variance. This implies that adopting financial technology facilitates access to financial services and enhances transaction efficiency, leading to better market reach and competitive advantage for MSMEs. However, the study is limited to MSMEs in Bali, which may restrict the generalizability of the findings to other regions. Additionally, the analysis did not include external factors such as government regulations and infrastructure limitations. Future research should expand the geographical scope and incorporate these external variables to obtain a more comprehensive understanding of FinTech's impact on MSMEs. The study suggests that stakeholders, including government and financial institutions, should encourage the adoption of digital financial services to enhance MSME competitiveness in an increasingly digital economy.